Perbedaan Penggunaan Paket Pembelajaran dan Motivasi Belajar terhadap Hasil Belajar Mata Kuliah Pengantar Pendidikan - Ariyanto, Dedy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine differences in the use of learning packages and learning motivation towards student learning outcomes in introductory courses in education. This study uses a quasi-experimental design using 2x2 factorial. The students involved in this study were 60 special education study program students, divided into 2 groups: the experimental group that was treated using a learning package and the control group that was not treated, namely using a textbook. The results obtained are 1). Fcount value of 54.079 was obtained with Sig. 0.021. Because the value of Sig. <0.05 then H0 is rejected and H1 is accepted, then it is concluded there is a difference between learning outcomes between those who use the Learning Package and those who use textbooks. 2). Obtained Fcount value of 4.980 with Sig. 0.030. Because the value of Sig. <0.05 then H0 is rejected and H1 is accepted, then it is concluded there is a difference between learning outcomes between students with high motivation and low motivation. 3). Obtained Fcount value of 1.796 with Sig. 0.047. Because the value of Sig. <0.05 then H0 is rejected and H1 is accepted, then it is concluded that there is a significant interaction between student learning outcomes using Learning Packages and textbooks as well as differences in motivation that have an influence on learning outcomes in Introduction to Education. Keywords: Learning Outcomes, Learning Motivation, Learning Packages